Perancangan dan Fabrikasi Mesin Pengolah Ubi Kayu untuk Produksi Makanan Ringan Lanting Kapasitas 40 kg/jam - Hariyanto, Satriawan Dini; Papasi, Rikson Gilbert; Munthohani, Ghoyali Rizyal; Lanekri, Irtifa Tashinudin; Sastika, I Putu (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2020)
The development of the food processing industry carried out by MSMEs in Indonesia is still largely dominated by traditional processing systems. A problem occurred in terms of the need for much labor to require higher production processes. An example of MSMEs that currently in promising development is the cassava chips snack industry. Many employees involved in the cassava chips production process, long production process, and the cassava chips (lanting) produced is a lack of uniformity. This study aims to design and fabricate a lanting extruder machine with a capacity of 40 kg/hour with a 0.5 HP electric motor. The FEA simulation results with the loading of 490.5 N using Autodesk Inventor 2020 software showed a maximum Von Misses stress of 17.68 MPa, a displacement of 0.04 mm, and a safety factor of 11.7.